Formação de professores e Análise do Comportamento: Caracterização de Necessidades Formativas para a Docência em Matemática na Educação Básica - Lopes, Jair [UNESP]; Peralta, Deise Aparecida [UNESP] (Associacao Brasileira de Psicologia, 2015)
In São Paulo, the implementation of the Mathematics Curriculum for Basic Education and Reference System for the Evaluation of Educational Achievement has determined the priority of teaching practices directly related to the development of skills and abilities. The aim of this paper was to present and discuss possible effects of deployment on the professional performance of teachers who teach mathematics and to present proposed research and intervention programs on the effects of it. From documentary analyzes, we found that a dense and varied set of actions that define the implementation of current public policy evaluation of school performance waived the investigation of the impact of measures on the prevailing behavioral repertoires of teachers responsible for effecting the same. It characterized the need to derive training of teachers or change the guidelines, information and activities proposed to conduct classes or relationships between events (actions of the students of the context and factors before whom such actions are important) expected as a result of exposure of students to teaching practices. Supported in recent literature of behavior analysis that describes the methodological procedures for making such derivation in the context of the National Curriculum Guidelines for demarcation of the Psychology about the future performance psychologist, is proposing the extension of such procedures in collaborative research and interventions with teachers as a strategy for learning development professionals with corresponding training needs indicated.
Teacher education and behavior analysis: Characterization of formative needs in teaching mathematics at basic education level
Keywords: Analysis of behavior; Teacher education; Teaching in mathematics